Structural Stability Analysis of Bridge Structure Using FEA (International Journal of Innovative Research in Engineering & Management, 2023)
In the current research, the dynamic  analysis of bridge structure is conducted to determine the  natural frequency and mode shape. The dynamic analysis is  conducted using ANSYS FEA simulation package. The  critical regions of high deformation and energy states are  determined. The analysis revealed the presence of several  dominant vibration modes, each associated with distinct  deformation patterns and nodal patterns. These findings  shed light on potential vulnerability zones and areas of  concern that may be susceptible to resonance and excessive  vibrations during bridge operation. Understanding these  critical modes is vital for designing appropriate damping  and vibration control measures to ensure the bridge's long term stability and safety.
Keywords: Bridge; modal; vibration; FEA; ANSYS FEA